2014
DOI: 10.1254/jphs.14037fp
|View full text |Cite
|
Sign up to set email alerts
|

Salidroside Attenuates Allergic Airway Inflammation Through Negative Regulation of Nuclear Factor-Kappa B and p38 Mitogen–Activated Protein Kinase

Abstract: Abstract. Salidroside is a biologically active ingredient of Rhodiola rosea, which has several interesting biological properties, including anti-oxidant and anti-inflammatory; however, its anti-allergic effects are poorly understood. The objective of this study is to determine whether salidroside attenuates the inflammatory response in an ovalbumin (OVA)-induced asthma model. OVA-sensitized/challenged mice show airway hyperresponsiveness (AHR) to inhaled methacholine and have an increased amount of T-helper2 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…As described previously, p38, one of three major MAPKs, has been considered to play a key role in allergic asthma and also been significantly implicated in corticosteroid insensitivity . Our study has shown that the augmentation of asthmatic symptoms as well as the phosphorylation of p38 MAPK after OVA challenge is significantly inhibited after the administration of SB203580, a selective p38 MAPK inhibitor.…”
Section: Discussionsupporting
confidence: 79%
“…As described previously, p38, one of three major MAPKs, has been considered to play a key role in allergic asthma and also been significantly implicated in corticosteroid insensitivity . Our study has shown that the augmentation of asthmatic symptoms as well as the phosphorylation of p38 MAPK after OVA challenge is significantly inhibited after the administration of SB203580, a selective p38 MAPK inhibitor.…”
Section: Discussionsupporting
confidence: 79%
“…Recently, monomers of Chinese traditional herbs have attracted more and more attention because of their desirable pharmacological effects. Many monomers from Chinese medicine were valuable in the treatment of asthma, such as baicalin [ 11 ], salidroside [ 12 ], astragalus membranaceus [ 13 ], and luteolin [ 14 ]. Although most of these monomers were investigated in murine models, their therapeutic effects shown on asthma are promising.…”
Section: Discussionmentioning
confidence: 99%
“…Salidroside treatment regulates the T helper 1 (Th1)/Th2 balance, which plays an important role in asthma. 12 These findings lay the foundation for the antiasthmatic property of salidroside. 11 Besides, another in vivo study reveals that salidroside treatment results in an inhibitory effect on asthmatic reactions, which was illustrated by the decreased AHR to inhaled methacholine, reduced levels of Th2 cytokines including IL-4, IL-5, and IL-13 and eosinophils in BALF and lung tissues.…”
Section: Introductionmentioning
confidence: 92%
“…11 Besides, another in vivo study reveals that salidroside treatment results in an inhibitory effect on asthmatic reactions, which was illustrated by the decreased AHR to inhaled methacholine, reduced levels of Th2 cytokines including IL-4, IL-5, and IL-13 and eosinophils in BALF and lung tissues. 12 These findings lay the foundation for the antiasthmatic property of salidroside. However, the effects of salidroside on airway remodeling have not been elucidated.…”
Section: Introductionmentioning
confidence: 92%